The Multifactorial Memory Questionnaire and Quality of Life: A Longitudinal Study in Parkinson’s Disease - Emily J. Corti; Natalie Gasson; Hayley Grant; Brayden Wisniewski; Andrea M. Loftus (Brain Sciences)
Background/Objectives: Objective memory decline is associated with poor quality of life (QOL) in Parkinson’s disease (PD, but it is unclear what role perception of memory (metamemory) plays. The Multifactorial Memory Questionnaire (MMQ) measures metamemory and is proposed to have a three-factor structure, but the factor structure of the MMQ in PD has not been explored. The current study examined (i) the factor structure of the MMQ in PD and (ii) the relationship between the metamemory and QOL in PD. Methods: This longitudinal, observational study involved 149 participants with PD (98 males, M age = 65.78 years, SD = 9.25). Participants completed the MMQ and the Unified Parkinson’s Disease Rating Scale (disease severity) at baseline, and the Parkinson’s Disease Questionnaire-39 (QOL) two years later. Results: Confirmatory factor analysis revealed both the three-factor and four-factor models were inadequate. Exploratory factor analysis resulted in a four-factor solution. The contentment and ability subscales from the original factor structure remained, while the strategies subscale was divided into external strategies and internal strategies. Disease severity, ability, and internal strategies uniquely predicted QOL. Individuals who reported low subjective memory ability and high use of internal strategies reported worse QOL two years later. Conclusions: These findings indicate that metamemory predicts QOL in PD and suggest that improved perceived memory ability and strategy use could offer avenues for improved QOL.